Deep phenotyping of peripheral tissue facilitates mechanistic disease stratification in sporadic Parkinson's disease. (April 2020) - Carling, Phillippa J; Mortiboys, Heather; Green, Claire; Mihaylov, Simeon; Sandor, Cynthia; Schwartzentruber, Aurelie; Taylor, Rosie; Wei, Wenbin; Hastings, Chris; Wong, Siew; Lo, Christine; Evetts, Samuel; et al.
Highlights: We undertook fibroblast-based deep phenotyping in sporadic Parkinson's disease (sPD). We identified distinct subgroups with mitochondrial or lysosomal dysfunction. Cellular dysfunction in fibroblasts was enhanced in fibroblast-derived neurons. Ursodeoxycholic acid rescued mitochondrial function in sPD. Abstract: Mechanistic disease stratification will be crucial to develop a precision medicine approach for future disease modifying therapy in sporadic Parkinson's disease (sPD). Mitochondrial and lysosomal dysfunction are key mechanisms in the pathogenesis of sPD and therefore promising targets for therapeutic intervention. We investigated mitochondrial and lysosomal function in skin fibroblasts of 100 sPD patients and 50 age-matched controls. A combination of cellular assays, RNA-seq based pathway analysis and genotyping was applied. Distinct subgroups with mitochondrial (mito-sPD) or lysosomal (lyso-sPD) dysfunction were identified. Mitochondrial dysfunction correlated with reduction in complex I and IV protein levels. RNA-seq based pathway analysis revealed marked activation of the lysosomal pathway with enrichment for lysosomal disease gene variants in lyso-sPD. Conversion of fibroblasts to induced neuronal progenitor cells and subsequent differentiation into tyrosine hydroxylase positive neurons confirmed and further enhanced both mitochondrial and lysosomal abnormalities. Treatment with ursodeoxycholic acid improved mitochondrial membrane potential and intracellular ATP levels even in sPD patient fibroblast lines with comparatively mild mitochondrial dysfunction. The results of our study suggest that in-depth phenotyping and focussed assessment of putative neuroprotective compounds in peripheral tissue are a promising approach towards disease stratification and precision medicine in sPD.